Security Constrained Unit Commitment Considering Spinning Reserve and Transmission Line Capacity Using Binary Particle Swarm Algorithm - Anton Frian Yohanes Reynaldo (Jurnal Teknik ITS, 2016)
Modern human nowadays couldn’t live and work effectively and efficiently without electricity. Electrical energy is an energy that really affects technology’s development and needs a system operation to generate and transmit the electricity. Power system operation in electrical system is expected to produce a reliable system and economically optimal to solve the fluctuative load condition in 24 hours. Unit Commitment (UC) could be used for on-off generation unit scheduling in the electrical system which is interconnected optimally. However, UC still could not do the unit scheduling by considering transmission line capacity. Security Constrained Unit Commitment (SCUC) is the development of UC with considering transmission line capacity as the calculation constraint. Particle swarm optimization algorithm is used to solve the SCUC. The application of SCUC by using particle swarm optimization is expected able to solve on-off generation unit scheduling, in case if the system couldn’t fulfill the security standard, which is considering the transmission line capacity. The result of this research is a generation unit scheduling calculation software that is more appropriate and meets the system standard.